2015
DOI: 10.1007/s00018-015-2087-8
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy programs: mechanisms and physiological implications of mitochondrial targeting by autophagy

Abstract: Mitochondria are an essential source of ATP for cellular function, but when damaged, mitochondria generate a plethora of stress signals, which lead to cellular dysfunction and eventually programmed cell death. Thus, a major component of maintaining cellular homeostasis is the recognition and removal of dysfunctional mitochondria through autophagy-mediated degradation, i.e., mitophagy. Mitophagy further constitutes a developmental program, and undergoes a high degree of crosstalk with apoptosis. Reduced mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
298
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 346 publications
(309 citation statements)
references
References 184 publications
(277 reference statements)
2
298
1
8
Order By: Relevance
“…The pathogenesis of PD, however, involves abnormalities in mitochondrial function, which include impaired mitochondrial electron transport chain function, damaged mitochondrial DNA, impaired calcium buffering, and abnormal mitochondrial morphology and dynamics [47]. Moreover, familial PD can be caused by mutations in genes that encode the proteins PINK (PTEN induced putative kinase 1), PRKN/PARK2 (parkin RBR E3 ubiquitin protein ligase) and PARK7/DJ-1 [8], each of which contribute to the selective removal of dysfunctional mitochondria by macroautophagy (autophagy hereafter). In this process, known as mitophagy, compromised mitochondria are flagged by autophagy receptors, recognized and engulfed by phagophores, which mature into autophagosomes, and delivered to lysosomes for degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of PD, however, involves abnormalities in mitochondrial function, which include impaired mitochondrial electron transport chain function, damaged mitochondrial DNA, impaired calcium buffering, and abnormal mitochondrial morphology and dynamics [47]. Moreover, familial PD can be caused by mutations in genes that encode the proteins PINK (PTEN induced putative kinase 1), PRKN/PARK2 (parkin RBR E3 ubiquitin protein ligase) and PARK7/DJ-1 [8], each of which contribute to the selective removal of dysfunctional mitochondria by macroautophagy (autophagy hereafter). In this process, known as mitophagy, compromised mitochondria are flagged by autophagy receptors, recognized and engulfed by phagophores, which mature into autophagosomes, and delivered to lysosomes for degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Mitophagy is a specific form of autophagy through which damaged or effete mitochondria are delivered to the lysosomes for hydrolytic and enzymatic degradation 9. Similar to autophagy, sequestration of mitochondria involves participation of autophagosomes or direct involvement of lysosomal membranes 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…Mitophagy is a dedicated form of autophagy that selectively removes damaged or old mitochondria, which has been identified from yeast to mammals as an important mitochondrial quality control pathway. 3 Of note, we recently reported for the first time that in C. elegans partial suppression of mitochondrial electron transport chain regulatory proteins (e.g. frataxin) extends lifespan through the activation of a pdr-1/ Parkin-, pink-1/ Pink-, and dct-1/ Bnip3-dependent mitophagy, which is promoted by the induction of a moderate iron starvation response (Fig.…”
mentioning
confidence: 92%
“…4 Several studies have shown that mitophagy defects are implicated in a wide array of human disorders including neurodegenerative diseases, myopathies and cancer. 3 Tumor development can result from alteration of basic cellular functions such as metabolism, differentiation, proliferation and death programs. In recent years, it has been accepted that autophagy, in addition to its cell survival function, can elicit cell growth inhibition and cell death functions thus playing a Janus faced role in promoting tumor cell survival or tumor regression respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation